The microeconomic impact of political instability: Firm‐level evidence from Tunisia. Issue 4 (27th April 2018) - Matta, Samer; Appleton, Simon; Bleaney, Michael
Abstract: This paper explores the impact of political instability on firms in the context of Tunisia, which experienced a surge in political instability events after the 2011 Jasmine revolution. Using a new dataset, we show that political instability was a major concern for small and exporting firms as well as those that were operating in the tourism sector, those that suffered from acts of vandalism or arson, and those that were located in the interior region of Tunisia. More importantly, we find strong evidence that political instability was the most damaging constraint to firm growth in Tunisia after the Arab Spring.